Strengthening the Capacity of Elected Women in Preparation of Village Level Planning in Women Led Panchayats Final Report - Planning Commission (Planning Commission, 2007)
The aim of the project on “Strengthening the capacity of Elected Women in the preparation of Village Level Planning in Women led Panchayats" funded by Planning Commission, Government of India enabled to identify the socio-economic resources available in the panchayats and strengthen the capacity of elected women to plan livelihood and employment by enabling to design Village Development Plan.
Planning Commission, Government of India
Planning Commission Government of India